VALIDATION OF A 5-MINUTE WEB CAMERA EYE-TRACKING COGNITIVE ASSESSMENT. (16th November 2018) - Gray, M; Gills, J; Smith, S; Bates, E; Glenn, J; Madero, E; Bott, N
Abstract: Alzheimer's disease is a form of dementia impacting memory and cognitive function in 131 million individuals worldwide. Early cognitive decline detection allows for earlier intervention, but valid and user-friendly assessment options are lacking. The purpose of this investigation was to validate a 5-minute web camera eye-tracking assessment for cognitive function. This prospective study included 49 adults (n=32 females, n=17 males; age=52.7 ± 27.3) who were divided into two age cohorts: older (ages 65+ years, n=25) and young-middle aged adults (ages 18–46 years, n=24). Of the older cohort, four had mild cognitive impairment (MCI) (Montreal Cognitive Assessment [MoCA] <26). Testing included the MoCA, NIH Toolbox cognitive assessments (Flanker Inhibitory Control and Attention, Dimensional Change Card Sort, Pattern Comparison Processing Speed [PCPS], and Picture Sequence Memory tests), Digit Symbol (DS), dual-task (habitual and fast), and 5-minute eye-tracking assessments. A Pearson's Correlation determined relationships between the NIH Toolbox cognitive assessments and the eye-tracking test and a one-way ANOVA determined differences between cognitively intact older adults and individuals with MCI. Significant correlations (p<.05) were found for the PCPS (r=.32), DS (r=.48), and dual-task (habitual: r=.52 and fast: r=.41). The eye-tracking assessment was able to discriminate between cognitively intact adults and individuals with MCI. These results suggest the 5-minute eye-tracking assessment is a valid method for assessing cognition among adults with and without cognitive impairment. The 5-minute eye-tracking test displayed convergent validity with currently used measures of cognition, indicating it may be a widely scalable option used in place of the longer traditional testing methods.